(untitled) (Journal of Applied Membrane Science & Technology, 2022)
A desalination is a promising approach to addressing the freshwater scarcity caused by limited freshwater resources and salt intrusion (pollution). Membrane distillation (MD) was proposed as a possible technology for desalination. This study review the efficiency of membrane distillation by comparing the permeate flux and thermal energy efficiency of the four configurations, namely, direct contact membrane distillation (DCMD), vacuum membrane distillation (VMD), air gap membrane distillation (AGMD) and sweeping gas membrane distillation (SGMD). It was observed that the sequence of permeate flux and thermal energy efficiency is VMD> DCMD> SGMD>AGMD and VMD> SGMD> AGMD> DCMD, respectively. The results show that the VMD provides the highest permeate flux at 15.2 kg/hm2 with 99.25% of salt rejection rate. Additionally, VMD possess good energy efficiency at 66% relative to other configuration at the recorded permeate flux. Subsequently, the feasibility of MD in desalination is studied using different case studies. Furthermore, the effect of operating parameters (feed temperature, feed concentration, feed flow rate, and long-term operation) on flux is discussed. The results suggested that the flux increases when feed temperature or feed flow is increased. At the same time, the flux will decrease when feed is in high concentration and long-term operation.